Crystal structure of 1,3-diisopropyl-4,5-dimethylimidazol-2-ylidene-N,N′-bis(1,3-bis(2,6-diisopropylphenyl)-1,3-dihydro-2H-1,3,2-diazaborol-2-yl)-l2-germenediamine, C63H94B2GeN8 - Wang Bing; Hu Yi-Fei; Wu Di (Zeitschrift für Kristallographie - New Crystal Structures)
C63H94B2GeN8, orthorhombic, P212121 (no. 19), a = 17.1750(7) Å, b = 19.1188(7) Å, c = 19.4359(8) Å, V = 6382.1(4) Å3, Z = 4, Rgt(F) = 0.0539, wRref(F2) = 0.1483, T = 170 K.